Introduction to bio-based packaging materials - Nazrin A.; Sapuan S.M.; Ilyas R.A.; Hawanis H.S.N.; Khalina A.; Jumaidin R.; Asyraf M.R.M.; Nurazzi N.M.; Norrrahim M.N.F.; Rajeshkumar L.; Atikah M.S.N. (De Gruyter, 2024)
Bio-based materials must be studied to replace polymers from petrochemical sources in packaging applications. However, using polymers from petrochemical sources has caused consumer and environmental concerns. Therefore, synthetic and nonsynthetic materials that can be used for packaging applications, scale-up methods, industrial uses, sustainability assessments, and end-of-life alternatives will all be included in this study. Synthetic polymers, e.g., polylactic acid (PLA), polyethylene furanoate (PEF), polybutylene succinate (PBS), and non-synthetic polymers, including waxes, lipids, proteins, starch, cellulose, and polyhydrodialkanoate (PHAs), are some of the bio-based compounds that will be covered in this work. Besides that, more attention is paid to surface modification techniques and coatings, multilayers, biocomposites, and additives used to modify material characteristics, particularly gas and moisture barriers and biodegradability. In sum, this research offers a comprehensive analysis of bio-based packaging materials, including processing, and an assessment of sustainability and available alternatives. 2023 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.